Corrosion characteristics of reduced activation ferritic-martensitic steel EUROFER by Li2TiO3 with excess Li. (May 2018) - Mukai, Keisuke; Sanchez, Fernando; Hoshino, Tsuyoshi; Knitter, Regina
Highlights: Corrosion of EUROFER RAFM steel by Li2 TiO3 with excess Li was investigated. Thick oxide double layer formed on the EUROFER plates at 823 and 1073 K, while the corrosion was limited at 673 K. Formation of the corrosion layer showed parabolic growth controlled by diffusion and linear growth caused by breakaway. The corrosion will not cause a significant impact on the mechanical strength of the blanket structural steel. Abstract: In a solid breeding blanket, ceramic breeder pebbles are in contact with reduced activation ferritic martensitic (RAFM) steel at high temperatures for years and accordingly form a corrosion layer on the blanket structural steel. Present study focuses on corrosion characteristics of EUROFER97 RAFM steel by an advanced breeder material of Li2 TiO3 with excess Li (initial ratio of Li/Ti = 2.2) at 623, 823, and 1073 K under sweep gas (He + 0.1% H2 ) flow. Formation of a thick oxide double layer was found on the surface of the EUROFER plates heated at 823 and 1073 K, while the corrosion layer formed at 673 K was < 1 µm even after 56 days. On the other hand, the changes that appeared on the contacted surface of the breeder pellet were insignificant. The growth of the corrosion layer shows that the corrosion caused by inward migrations mainly of Li and O from the breeder material will have little influence on mechanical property of the blanket structural steel.